2020
DOI: 10.1136/jitc-2019-000376
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of plasma exosomal microRNAs with the efficacy of immunotherapy inEGFR/ALKwild-type advanced non-small cell lung cancer

Abstract: BackgroundImmunotherapy has become an important treatment option for patients with advanced non-small cell lung cancer (NSCLC). At present, none of these existing biomarkers can effectively stratify true responders and there is an urgent need for identifying novel biomarkers. Exosomes derived from the serum of patients with cancer have been proven to be reliable markers for cancer diagnosis. Here, we explored the possibility of using plasma-derived exosomal microRNAs as potential biomarkers for optimal selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 43 publications
7
92
0
1
Order By: Relevance
“…The authors identified three members of the miRNA-320 family (miRNA-320b, miRNA-320c and miRNA-320d) as potential biomarkers for predicting the efficacy of immunotherapy in advanced NSCLCs. In addition, the authors showed that miRNA-125b-5p was downregulated in the post-treatment exosome plasma compared to baseline samples of the patients experiencing a partial response [181].…”
Section: Exosomesmentioning
confidence: 99%
“…The authors identified three members of the miRNA-320 family (miRNA-320b, miRNA-320c and miRNA-320d) as potential biomarkers for predicting the efficacy of immunotherapy in advanced NSCLCs. In addition, the authors showed that miRNA-125b-5p was downregulated in the post-treatment exosome plasma compared to baseline samples of the patients experiencing a partial response [181].…”
Section: Exosomesmentioning
confidence: 99%
“…Among them, it was found that low levels of exosome-derived hsa-miR-320d, hsa-miR-320c, and hsa-miR-320b may indicate the better efficacy of PD-1/PD-L1 immunotherapy in advanced NSCLCs. In addition, when hsa-miR-125b-5p, a T-cell suppressor in exosomes, is downregulated during immunotherapy, NSCLC patients may gain enhanced T-cell function and respond well [154].…”
Section: Exosome-based Immunotherapy In Animal Modelsmentioning
confidence: 99%
“…However, the role of miRNAs in personalized cancer treatment has been not fully elucidated yet. A study conducted by Peng et al [ 23 ] revealed that three miRNAs (hsa-miR-320d, hsa-miR-320c, hsa-miR-320b) might predict immunotherapy response in non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%